1995
DOI: 10.1079/bjn19950039
|View full text |Cite
|
Sign up to set email alerts
|

Variation in food group and nutrient intake with day of the week in an elderly population

Abstract: The present paper is an analysis of 138 5-or 7-d diet diaries collected from a free-living population of people aged 68-90 years in Norwich. Men had higher intakes than women of energy and most nutrients, but patterns of variation across the week were similar for both sexes. Intakes of meat, meat products, fish and vegetables varied across the week both in frequency and amount eaten, but the other main food groups showed no significant variation. Alcohol was taken more frequently at weekends but the amount did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 8 publications
3
28
0
2
Order By: Relevance
“…Thomson et al (1988) found increased intakes of alcohol and energy at weekends in a group of Scottish men. Maisey et al (1995) reported that in an elderly British population the alcohol intake was higher on Saturdays and Sundays than during weekdays. In the current survey, the intake of alcohol was most abundant on Fridays and Saturdays which can be explained by cultural differences in drinking habits and by the fact that on Sundays most of our subjects had to anticipate for the next working day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thomson et al (1988) found increased intakes of alcohol and energy at weekends in a group of Scottish men. Maisey et al (1995) reported that in an elderly British population the alcohol intake was higher on Saturdays and Sundays than during weekdays. In the current survey, the intake of alcohol was most abundant on Fridays and Saturdays which can be explained by cultural differences in drinking habits and by the fact that on Sundays most of our subjects had to anticipate for the next working day.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Maisey et al (1995), the intakes of meat, meat products, ®sh and vegetables varied across the week. The intakes of protein, fat and total energy were higher at weekends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All food and drink consumed over 7 days was recorded using the 'precise individual weighing' method 14 . Data were recorded under the same conditions at all three centres, i.e.…”
Section: Dietetic Studymentioning
confidence: 99%